Electrospinning of 1D Fiber‐Like Block Copolymer Micelles with a Crystalline Core. Issue 19 (21st August 2022) - Ellis, Charlotte E.; Hils, Christian; Oliver, Alex M.; Greiner, Andreas; Schmalz, Holger; Manners, Ian
Abstract: Electrospinning is a simple, low‐cost, and high throughput technique that allows for the processing of polymers into fibers. The process can be controlled to allow access for well‐defined continuous fibers that are of interest for a wide range of applications including as tissue scaffolds, as nanowires in optoelectronic devices, and in catalysis. Conventional electrospinning processes use polymer solutions with high molecular weights. Here, the electrospinning of 1D fiber‐like block copolymer micelles containing a crystalline core is reported. The successfully accessed core‐shell microfibers in which 1D micelles containing a crystalline poly(ferrocenyldimethylsilane) (PFS) core are immobilized on a polystyrene microfiber via coaxial electrospinning. Furthermore, efforts to extend this approach to the use of 1D micelles comprising of a crystalline, π ‐conjugated poly(di‐ n ‐hexylfluorene) (PDHF) core are described. Electrospinning is also successfully used to prepare microfibers consisting solely of 1D micelles with a PFS crystalline core, the first examples where a template material is not required. Abstract : The electrospinning of 1D fiber‐like block copolymer micelles containing a crystalline core is investigated by means of coaxial and convention electrospinning methods. Electrospinning is successfully used to prepare microfibers consisting solely of 1D micelles with a poly(ferrocenyldimethylsilane) (PFS) crystalline core, demonstrating the first example where a template or carrier material is not required.